ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PERBANKAN PADA BANK UMUM DI BURSA EFEK INDONESIA - Pratiwi, Septiana Icha; Sulistiyani, Tina (Universitas Ahmad Dahlan, 2014)
This research is aimed to obtain empirical evidence on the factors affecting the distribution of bank credit. There are many factors affecting the distribution of bank credit. However, this research was only limited by dominant factors affecting the distribution of bank credit obtained from bank credit theories and the results from previous research studies. Therefore, factors which were the selected independent variables in this research were Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Assets (ROA), and Loan to Deposit Ratio (LDR). While the dependent variables were the distribution of bank credit which was proxied by Loan to Asset Ratio (LAR) variable. The results of the research indicates that simultaneously, the variables of DPK, CAR, NPL, ROA, dan LDR significantly affectÂ the distribution of bank credit in the period 2010-2012. While partially, a result was obtained that DPK, NPL, and LDR variables significantly affect the distribution of bank credit. Meanwhile CAR and ROA variables do no significantly affect the distribution of bank credit in the period 2010-2012